The characteristics of the river network of the Wadi Al-Dabaa basin, northeast of Maysan Province , using RS & GIS - Latif G.Farhan / Hussain Joban Uraybi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2023)
The research aims to study the characteristics of the river network of the Wadi Al Dabaa basin, northeast of Maysan Governorate, using data Remote sensing and geographic information systems, and through the integration between remote sensing data and GIS software, which are two tools of great importance in drawing the geomorphological map of land forms and showing the characteristics of the river network in the basin through remote sensing data and the contrast of reflectivity between land features in Space visuals and GIS software, which includes many quantitative and statistical programs and methods that are related to GIS tools. In addition to the field study of the lands of the basin, as these modern means and methods in the study of river basins are considered to produce accurate scientific data that can be used in achieving economic development in the region, given that the landforms that cover the lands of the basin contribute to the abundance of many reliable economic resources in The development of the region, as well as the characteristics of the river network in the basin and the amount of water drainage it provides for agricultural operations in the region. Tectonic structural processes were subjected to external processes that changed their original features, especially the processes of weathering, erosion and gravity, as well as what the natural characteristics that characterize the region (such as rain and the topographical factor that includes the degree of slope and the shape of the slope and the ground system and the shape of the land) which have effectively contributed to The activity of external processes, especially Morphe-climatic processes (water erosion) in particular, or as a result of the operation Evaporative methods that are related to climate characteristics, drought conditions, soil components, and the level and quality of groundwater in the region. In the lands of the basin, the study also showed that the area of   the basin amounted to (21.5) km2, a length of (8.7) km and a width of (2.5) km, and the circumference of the basin amounted to (49.6) km, while the study showed that the characteristics of The river network of the basin, especially the river levels, were (6) ranks, the total of their courses was (2448) streams, varying in the number of their courses and their lengths, as their numbers reached the six ranks, respectively (1406, 512, 244, 153, 123, 1) streams, and their lengths were The total basin courses for all grades amounted to (152.8) km, and their lengths vary in the river grades of the basin, respectively (99.53, 26.26, 12.69, 7.72, 6.14 and( 0.46) km, and the highest level was In the basin (174) meters and the lowest level (56) m, .